Site index - The Editors, - (Nordic Archaeological Abstracts - NAA, 1979)
The specific names of sites are listed for castles, churches, towns, and well-known find localities. The same of the relevant county, district, or region according to the map is always listed, except when the paper deals with a larger area. General surveys may be found under SURVEY in the Subject index. The Scandinavian names are always used, i e København, not Copenhagen. For the area outside the Nordic the name of the country is listed as are well-known find localities.